Performance of F2 Generation Lines of Soybean (Glycine max. L) as Backcross Results of GHJ-4 and GHJ-5 with Ryoko as A Donor Parent - Sjamsijah, Nurul; Rahayu, Sri; Rosdiana, Eva; Santika, Putri; Asmono, Sepdian Luri (Journal of Applied Agricultural Science and Technology, 2023)
The breeding of new high-yielding varieties is one of the solutions to the low productivity of soybeans in Indonesia. Superior genotypes of ‘GHJ-4 (A)’ and ‘GHJ-5 ’ were obtained in the previous study with an average weight of 13 g/100 seeds and a potential yield of 3 tons/ha. The attempt to increase the weight and size of the seeds of ‘GHJ-4’ and ‘GHJ-5’ was continued using the backcrossing method with ‘Ryoko  (>35 g/100 seeds) as a parent donor. F1 plants were obtained with an average weight of 15 g/100 seeds. This study aimed to determine the performance of the F2 generation of backcross in terms of the number of filled pods, the weight of 100 seeds, yield per plant (g), yield per plot (kg), and potential yield per hectare (tons/ha), as well as the heritability value of the genotypes. In this particular study, the F2 seeds from F1 plants were then planted and observed. This study used a non-factorial randomized block design (RBD) with 11 soybean genotypes, each consisting of 3 replications. The results showed that the F2 generations (GHJ-4XRyoko, RyokoXGHJ -5, and GHJ-4XGHJ-5) are considered as prospective new high-yielding varieties with a potential yield of ≥ 3.5 tons/ha, which have successfully restored the trait of ‘Ryoko’ and surpassed the performance of ‘GHJ-4’ and ‘GHJ-5’ as their parents in all parameters. The heritability value of the genotypes tested belongs to the high category, on the parameters of the number of filled pods (96.937 %), yield per plant (98.102 %), the weight of 100 seeds (99.132%), yield per plot (92.605 %) and potential yield per hectare (92.257 %).  For the parameters observed, the back cross yields of harvest age were 72-74 HST, the weight of 100 grains was 17-18 grams and the yield per hectare was around 4 tons/ha. The heritability value shows that the observed traits are inherited from parents on average more than 90% and the selection that will be used is pedigree selection.